Two new species and additional records of Lathrobium Gravenhorst (Coleoptera: Staphylinidae: Paederinae) from Guangxi, South China - Peng, Zhong; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2013)
Material of the paederine genus Lathrobium Gravenhorst, 1802 from the Chinese province of Guangxi is examined. Five apterous species are identified, two of which are described as new to science: L. damingense Peng & Li sp. n. (Daming Shan) and L. hujiayaoi Peng & Li sp. n. (Maoer Shan). The female sexual characters of L. proprium Peng & Li are described and illustrated for the first time. With the newly described species in this paper, the Lathrobium fauna of Guangxi constitutes 9 species, that of the entire mainland China 168 species.